Non-coercive influence: Scale development and validation based on resource and relational paradigms. Issue 3 (June 2019) - Mishra, Manit; Banerjee, Mohua
Abstract: To overcome competition in an increasingly network dependent market, retailers are required to influence upstream channel partners while sustaining relationships. However, the contemporary supply chain literature has not sufficiently leveraged the resource and relational paradigms to examine influence. Grounded on resource dependency theory and commitment-trust theory paradigms, this study describes conceptualization and operationalization of a 12-item scale for measuring non-coercive influence on upstream channel partners in retail supply chain management (R-SCM) context. The study is based on responses from 547 retail professionals in India obtained over four successive surveys. Psychometric properties were assessed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The proposed scale demonstrates construct validity. Invariance-testing carried out over 4-levels of increasingly demanding equivalence confirmed cross-validation. Nomological validity of the scale was tested by evaluating association with suppliers' intention to cooperate. The results indicate existence of three dimensions of non-coercive influence: collaborative intent, market intelligence dissemination, and operational support. Retailers can use the scale to assess their personnel's non-coercive influence behavior over suppliers. Highlights: Grounded on resource dependency theory (Pfeffer and Salancik, 1978 ) and commitment-trust theory (Morgan and Hunt, 1994 ). The study, based on responses from 547 retail professionals, conceptualizes and operationalizes the construct non-coercive influence. Results indicate existence of three dimensions of non-coercive influence: Collaborative intent, Market intelligence dissemination, and Operational support. 12-item scale for measuring retail professionals' non-coercive influence behavior over suppliers in retail supply chain management (R-SCM) context is presented. Construct validity was established through confirmatory factor analysis (CFA) followed by cross-validation using invariance-testing, and nomological validity.